2022
DOI: 10.1093/texcom/tgac049
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of multisensory features of two auditory cortical areas: primary (A1) and higher-order dorsal zone (DZ)

Abstract: From myriads of ongoing stimuli, the brain creates a fused percept of the environment. This process, which culminates in perceptual binding, is presumed to occur through the operations of multisensory neurons that occur throughout the brain. However, because different brain areas receive different inputs and have different cytoarchitechtonics, it would be expected that local multisensory features would also vary across regions. The present study investigated that hypothesis using multiple single-unit recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 67 publications
(103 reference statements)
2
8
0
Order By: Relevance
“…Thus, the observed non-integrative effects could not have been induced by inhibitory effects of one stimulus being presented outside of its receptive field. Numerous reports have documented and examined non-integrated multisensory responses in bimodal neurons in a variety of neural areas (Perrault Jr et al , 2005;Meredith et al , 2021;Merrikhi et al , 2022a;Merrikhi et al , 2022b). The present study shows that such non-integrative multisensory effects were strongly influenced by development because, as depicted in Figure 5D, significant shifts were seen from primarily suppressive levels in infants to progressively higher levels of multisensory response change across the periods of adolescence.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Thus, the observed non-integrative effects could not have been induced by inhibitory effects of one stimulus being presented outside of its receptive field. Numerous reports have documented and examined non-integrated multisensory responses in bimodal neurons in a variety of neural areas (Perrault Jr et al , 2005;Meredith et al , 2021;Merrikhi et al , 2022a;Merrikhi et al , 2022b). The present study shows that such non-integrative multisensory effects were strongly influenced by development because, as depicted in Figure 5D, significant shifts were seen from primarily suppressive levels in infants to progressively higher levels of multisensory response change across the periods of adolescence.…”
Section: Discussionsupporting
confidence: 50%
“…We also examined the subthreshold form of multisensory neuron across the different age groups. Although small in occurrence (as also observed in other areas - (Meredith et al , 2021;Merrikhi et al , 2022a;Merrikhi et al , 2022b), their proportions showed an increasing trend during development but no developmental pattern for changes in MSI levels were demonstrated. A similarly low incidence of multisensory response depression revealed the presence of the effect during development, but consistent changes across development could not be assessed.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, the organisational patterns observed for sensory responses in hearing animals was not observed. Specifically, for hearing DZ, visual responses were segregated posteriorly in the structure, presumably near the sources of visual cortical inputs, whereas somatosensory responses were clustered anteriorly, near presumed sources of somatosensory cortical inputs (Merrikhi et al, 2022, 2023). In contrast, no distributional trends were observed for visual or somatosensory responses in the early‐deaf DZ that essentially filled the entire extent of the region.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory response features of DZ include longer latency responses and broader frequency tuning than found in A1, as well as responses to complex auditory cues (He et al, 1997; Stecker et al, 2005). In addition, a large proportion (>76%) of DZ neurons exhibit visual and/or somatosensory influences that were differentially distributed in the region (Merrikhi et al, 2022, 2023). Furthermore, approximately 57% of neurons showed multisensory convergence, of which many demonstrated multisensory integration in response to multisensory stimulation.…”
Section: Introductionmentioning
confidence: 99%